Analysis Of The Determinant Factors Of Inpatient Nurses' Work Productivity At Gambiran Regional Hospital Kediri - Titin Susanti; Ayu Ika Fitrianingtias (Journal for Quality in Public Health, 2025)
Nurses are the cornerstone of healthcare systems, responsible for delivering nursing care, ensuring patient safety, improving satisfaction, and maintainingcontinuity of medical services. This study aimed to examine the effect of workload, motivation, and compensation on the productivity of 117 inpatient nurses at Gambiran Regional General Hospital. The study design was quantitative, cross-sectional, where the independent and dependent variables were measured simultaneously. The results of the Kolmogorov-Smirnov normality test showed a non-normal distribution (sig = 0.00 < 0.05), so the correlation analysis used the non-parametric Spearman Rho test. The results showed that the three independent variables had a positive and significant effect on the productivity of inpatient nurses at Gambiran Regional General Hospital with significance values of 0.018, 0.000, and 0.050, respectively. Motivation proved to be the strongest predictor with the highest correlation coefficient (0.360), followed by workload (0.246) and compensation (0.205). Nurse productivity is a synergistic result of strong motivation, optimal workload management, and a fair compensation system. Managerial implications suggest a focus on performance-based compensation evaluation and strengthening motivation.